Asthma - Biological Evidences 2019
DOI: 10.5772/intechopen.85114
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Platelets in Allergic Inflammation and Asthma

Abstract: Platelets are a kind of blood cells derived from bone marrow megakaryocytes and play essential roles in thrombosis, hemostasis, and tissue repair. Platelets have been found to be crucially involved in various immune responses and actively involved in the pathogenesis of allergic diseases such as allergic asthma. Patients with allergic asthma have lower platelet counts and increased levels of markers of platelet activation after allergen exposure. Platelets have been found extravascularly in the airways, and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…12,13 Moreover, increased levels of platelet-derived mediators have been noted in peripheral blood and bronchoalveolar lavage fluid (BALF) of asthmatic patients, suggesting increased levels of platelet activation. 14 Conclusions: This study demonstrates that platelet lipid, mRNA, and protein content is different according to allergy severity. These findings suggest that platelet load is a potential source of biomarkers and a new chance for therapeutic targets in severe inflammatory pathologies.…”
Section: Introductionmentioning
confidence: 79%
“…12,13 Moreover, increased levels of platelet-derived mediators have been noted in peripheral blood and bronchoalveolar lavage fluid (BALF) of asthmatic patients, suggesting increased levels of platelet activation. 14 Conclusions: This study demonstrates that platelet lipid, mRNA, and protein content is different according to allergy severity. These findings suggest that platelet load is a potential source of biomarkers and a new chance for therapeutic targets in severe inflammatory pathologies.…”
Section: Introductionmentioning
confidence: 79%
“… 16 Moreover, increased levels of platelet‐derived mediators have been noted in peripheral blood and bronchoalveolar lavage fluid (BALF) of asthmatic patients, suggesting increased levels of platelet activation. 17 We previously found that severe food‐associated respiratory allergy could be associated with the alteration of platelet functions. 7 Since then, our aim had been to study platelet phenotype and role in severe allergic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Activated platelets and platelet-activating factor (PAF), as a potent inflammatory mediator released by inflammatory cells such as macrophages, neutrophils, eosinophils, platelets and endothelial cells, play an important role in the pathogenesis of inflammatory diseases through the induction of inflammatory mediators ( Table 7 ) that: (1) stimulate vascular endothelial cells to produce cytokines (e.g., IL-1 and IL-18) and platelet expression of CD40/CD40 ligands to promote increased thrombotic activity; (2) stimulate the synthesis of lipid mediators (TXA2, hydroxy-eicosatetraenoate (12-HETE) and PAF); (3) release peptide 2 (activates neutrophils), sphingosine 1-phosphate, growth factors (PDGF and TGF-β), nitric oxide (NO), cytokines (IL-1β and IL-7) and chemokines (CXCL5, MCP-3, RANTES, MIP-1α, platelet factor 4); (4) proinflammatory mediators such as histamine, serotonin; (5) growth-regulating oncogene α (GRO-α); (6) high-mobility group box 1 and P-selectin. The expression of CD40/CD40 ligand on activated platelets is crucial in antigen presentation to effector cells (T lymphocytes), maturation and activation of DCs and production of T-dependent isotype switching as well as interaction between other immune cells such as B cells, T cells, neutrophils, macrophages, endothelial cells, NK cells and DCs [ 30 , 40 ]. PAF plays an important role in inflammatory and thrombotic diseases and in both immune-mediated and non–immune mediated anaphylaxis.…”
Section: Development Of Allergic Inflammationmentioning
confidence: 99%
“…Increased levels of blood markers of activated platelets (PF4, P-selectin, β-thromboglobulin (β-TG), and PMP) have been observed in numerous human diseases, including systemic lupus erythematosus (SLE), systemic sclerosis (SSc), and small vessel vasculitis, AD and psoriasis, but also in a mouse model of AD. Some of the platelet factors including histamine, 5-HT, acid proteases, IL-1β, TGF-β, PAF and prostaglandin E2 induce pruritus and bleeding in AD [ 39 , 40 , 41 ]. The interaction of platelets with the endothelium and leukocytes leads to the activation of platelets and increased deposition of fibrin by platelets, as well as stimulation of neutrophils in the release of chromatin and formation of extracellular traps (NETs), which directly promote activation and aggregation of platelets [ 42 ].…”
Section: Development Of Allergic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation